1992
DOI: 10.1007/bf00230328
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic restoration of microsomal lipids and enzyme changes in HMG-CoA reductase and Acyl-CoA : cholesterol acyltransferase in chick liver

Abstract: We have studied the correlation between changes in the lipid composition in chick liver microsomes and the activities of 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CoA reductase) and acyl-CoA: cholesterol acyltransferase (ACAT) by in vivo and in vitro experiments with 21-day-old chicks. A 5% cholesterol diet for 3 hr produced an increase in the microsomal and plasmatic cholesterol content, a decrease in HMG-CoA reductase activity and a concomitant increase in ACAT activity. The effect produced by the short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…After absorption, FC and fatty acids are re-esterified in enterocytes by ACAT (39) . High levels of cholesterol supplementation significantly improved the hepatic microsomal ACAT activity in the present study, which is consistent with in vivo studies on chicks (44) , pigs (45) and rats (46) . The in vitro addition of cholesterol to microsomal fractions significantly increases ACAT activity (47,48) .…”
Section: Cholesterol Metabolism and Homeostasissupporting
confidence: 92%
“…After absorption, FC and fatty acids are re-esterified in enterocytes by ACAT (39) . High levels of cholesterol supplementation significantly improved the hepatic microsomal ACAT activity in the present study, which is consistent with in vivo studies on chicks (44) , pigs (45) and rats (46) . The in vitro addition of cholesterol to microsomal fractions significantly increases ACAT activity (47,48) .…”
Section: Cholesterol Metabolism and Homeostasissupporting
confidence: 92%
“…This difference between different species could be mainly related to the cholesterol level in the diet. Stimulation of acat expression by a moderately high dietary cholesterol supplementation was also observed in chicks [48], guinea pigs [49], and rats [50]. In in vitro studies, it was also observed that the activity of ACAT can be increased by the addition of cholesterol to microsomal fractions [51,52].…”
Section: Regulation By Dietary Cholesterol Levelsmentioning
confidence: 82%
“…Previous reports suggested that function of this enzyme can be regulated by multiple nutritional factors. The activity of SOAT1 is increased by dietary cholesterol supplementation in young chick liver [ 7 ]. The activity of liver SOAT1 is inhibited by dietary n-3 polyunsaturated fatty acids in rabbits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%